Prevalence and Safety of Left-Footed Driving Following Right Foot Surgery Patients Including a Driving Simulation. (July 2019) - McKissack, Haley M.; Chodaba, Yvonne E.; Bell, Tyler R.; Lehtonen, Eva J.; Araoye, Ibukunoluwa B.; Shah, Ashish B.; Stavrinos, Despina; Johnson, Michael D.
Background: For many patients, returning to driving after right foot and ankle surgery is a concern, and it is not uncommon for patients to ask if driving may be performed with their left foot. A paucity of literature exists to guide physician recommendations for return to driving. The purpose of this study was to describe the driving habits of patients after right-sided foot surgery and assess the safety of left-footed driving using a driving simulator. Methods: Patients who underwent right foot or ankle operations between January 2015 and December 2015 were retrospectively identified. A survey assessing driving habits prior to surgery and during the recovery period was administered via a REDCap database through email or telephone. Additionally, simulated driving scenarios were conducted using a driving simulator in 20 volunteer subjects to compare characteristics of left- versus right-footed driving. Results: Thirty-six of 96 (37%) patients who responded to the survey reported driving with the left foot postoperatively. No trends were found associating left-footed driving prevalence and socioeconomic status. In driving simulations, patients exceeded the speed limit significantly more ( P < .001) and hit other vehicles more ( P < .026) when driving with the right foot than the left. The time to fully brake and fully release the throttle in response to vehicular hazards was significantly prolonged in left-footed driving compared with right ( P = .019 and P = .034, respectively). Conclusion: A significant proportion of right foot ankle surgery patients engaged in left-footed driving during postoperative recovery. Driving with both the right and left foot presents a risk of compromised safety. This study provides novel objective data regarding the potential risks of unipedal left-footed driving using a standard right-footed console, which indicates that driving with the left foot may prolong brake and throttle release times. Further studies are warranted for physicians to be able to appropriately advise patients about driving after foot and ankle surgery. Level of Evidence: Level IV, case series.